دراسة الخصائص الضوئية للفرايت– باستخدام تقنيات IR , Vis/UV - حلبي محمد; الأعرج بدر (Latakia University Journal -Basic Sciences Series, 2018)
حُضِّر مسحوق الفرايت ،حيث (x = 0.5) بالطريقة السيراميكية التقليدية ثنائية التلبيد، وحصلنا على طيف IR لهذه العينة في المجال (400-1000) cm-1 ، ثم حددنا ضمن هذا المجال، ترددات اهتزاز المواقع الرباعية، والمواقع الثمانية، في بنية الفرايت ، وقرينة الانكسار، ومعامل التوهين. وكذلك حصلنا على طيف الامتصاص والانعكاس في المجال (200 – 800) nm الخاص بالضوء المرئي وفوق البنفسجي علاوة على ذلك تم تعيين الطول الموجي من طيفي الامتصاص والانعكاس، الذي تحصل عنده كلتا الظاهرتين ، كذلك حددت طاقة الفجوة الضوئية، عند درجة حرارة الغرفة. powder Ferrite (where x=0.5) was prepared by a well-known conventional ceramic double sintering method. Then, the IR-spectrum for this sample was taken in the range (400-1000) cm-1. The vibration band frequencies of the tetrahedral and octahedral sites in the structure of Ferrite, refractive index and attenuation coefficient were determined .In addition, the absorption and reflection spectra were taken in the range (200 – 800) nm by means of Vis/UV spectrophotometer from which the wave length at both phenomena was extracted. Furthermore, the optical gap energy of sample was found at room temperature.